1996
DOI: 10.1136/bmj.312.7046.1567
|View full text |Cite
|
Sign up to set email alerts
|

Teenagers' knowledge of emergency contraception: questionnaire survey in south east Scotland

Abstract: Objective-To determine the level of knowledge of emergency contraception among 14 and 15 year olds.Design-Confidential questionnaire survey. Setting-10 secondary schools in Lothian, south east Scotland.Subjects-1206 pupils predominantly (98.7%) aged 14 and 15 in the fourth year of secondary school.Main outcome measures-Knowledge of the existence of emergency contraception; of its safety, efficacy, and time limits; and ofwhere to obtain it.Results-1121 (93.0%Y.) fourth year pupils aged 14-16 had heard of emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 7 publications
6
48
1
Order By: Relevance
“…School was the most commonly cited source of sex education (24.3%). This is similar to findings in a study conducted in south east Scotland [19]. Partners' approval contributes significantly to emergency contraceptive use.…”
Section: Discussionsupporting
confidence: 80%
“…School was the most commonly cited source of sex education (24.3%). This is similar to findings in a study conducted in south east Scotland [19]. Partners' approval contributes significantly to emergency contraceptive use.…”
Section: Discussionsupporting
confidence: 80%
“…The percentage of women who had previous abortions (44%) was similar to that reported in other studies 16,17,27,29 . Women who are seeking abortion are at risk of future unintended pregnancy and should receive sufficient information regarding EC and encouragement to use more effective regular contraceptive options following an abortion.…”
Section: This Study Provides Detailed Information About Women's Knowlsupporting
confidence: 89%
“…We do not think this age difference influenced the results of the study, and if anything, women in group 1 should have had more information about the ECP as they were younger. This differential in knowledge related to age has been reported in other studies [15][16][17][18][19][20] suggesting that the younger generation is better informed about current contraceptive options probably through improved sex education programmes in schools 20 .…”
Section: This Study Provides Detailed Information About Women's Knowlsupporting
confidence: 59%
“…14 A study in Scotland showed that one third of sexually experienced students had used emergency contraception; a number which is very high compared to our population. 15 In a Swedish study, among all teenagers who had had sexual intercourse, one in four stated that they had used emergency contraception. This study revealed that the maximal time span between unprotected intercourse and initiation of treatment was not readily recognized.…”
Section: Discussionmentioning
confidence: 99%